Medication Appropriateness in Elderly Patients Diagnosed with Pneumonia: Pharmaceutical SciencePharmacy Practice - Pandey, Meenu; Meera, N.K. (International Journal of Life Science and Pharma Research, 2022)
Ageing is a natural process accompanied with compromised good health. Pneumonia is associated with several independent risk factors, including the severity of clinical presentation, age, comorbidities, and specific pathogens which increase the burden of morbidity, mortality in aged patients. This study was carried out to assess the appropriateness of therapy for pneumonia in elderly patients. A prospective, observational study was conducted from July 2018 to June 2021 in the department of pulmonary medicine of a tertiary care teaching hospital in Bangalore, India. A total of 90 elderly patients aged >65 years, diagnosed with pneumonia who fulfilled study criteria and consented to take part in the study were enrolled. A well designed and internally validated case report form was used to document the findings after a due approval from the Institutional Ethics Committee. Socio-demographic characteristics, prescribed medications and clinical characteristics were documented and analyzed. Out of the 90 elderly patients, 25.6% were male while 75.4% were female. The mean age of the participants was 70.03±5.26 (SD) years. Applying tools like START/STOPP criteria, Beers criteria and MAI index, it was found that, 16.7% were received incorrect dose, 12.22% received drug duplication, 3.3% received drug which was not indicated, 2.2% received drug which was not effective for that condition and in 1.1% patients did not receive drugs for required duration. The findings from this study provide the feedback to the healthcare team to ensure rational management of pneumonia in elderly patients and enable this vulnerable population with improved health related quality of life.